Prognostic factors following enucleation of 111 uveal melanomas. Issue 11 (November 1993) - Coleman, K; Baak, J P; Van Diest, P; Mullaney, J; Farrell, M; Fenton, M
Abstract : Follow up information was retrieved on 111 patients who underwent enucleation for uveal melanoma between 1964 and 1987, allowing a minimum postoperative period of 5 years. Univariate survival analysis was carried out using Kaplan-Meier curves and the differences between the curves were analysed with the Mantel-Cox test. Multivariate analysis used the Cox proportional hazards model. Univariate analysis isolated each of the following as significant prognosticators: largest tumour diameter (LTD) (p < 0.002), presence of epithelioid cells (p < 0.03), and glaucoma (p < 0.001). A combination of cell type, glaucoma, and LTD (p < 0.0001) had strong and independent prognostic significance in multivariate analysis. The results of this series are compared with previous studies and the value of cell type information and new quantitative parameters is discussed.